Մուշեղ իշխան. հայապահպանության նվիրյալը - Էվելինա Բաղդասարյան (ՀՀ ԳԱԱ հրատ.)
Писатель, педагог, представитель западно-армянской диаспоры Мушег Ишхан (1914–1990) своими произведениями и общественной деятельностью в диаспоре боролся за сохранение армянского языка, армянской идентичности, ее облика и своеобразия. В его публицистических статьях, в поэтическом сборнике “Аревамар”, в драме “Паруйр Айказн и Мовсес Хоренаци” звучит большая тревога по поводу национального отчуждения. Poet, pedagogue and representative of Western Armenian Diaspora Mushegh Ishkhan (1914–1990) has fought for the preservation of the Armenian language, national identity, type and image through his poetry. The poet sounds the alarm of assimilation through his articles, the “Arevamar” collection of poems, in the drama “Paruyr Haykazn and Movses Khorenatsi” and other works.
Keywords: Biography; Literature; Auxiliary Sciences of History; Language and Literature